A Diagnostic Challenge: Risk Factors and Surgical Treatment of Laryngeal Chondroradionecrosis - Başaran, Bora; Doruk, Can; Çaytemel, Berkay; Ünsaler, Selin; Ünsaler, Selin; Şen, Cömert; Aslan, İsmet (ENT Updates, 2022)
Objectives: Thirteen cases of laryngeal chondroradionecrosis unresponsive to conser- vative treatment and treated with laryngectomy were presented with an analysis of possible risk factors. Methods: Retrospective analysis of 13 patients operated on for chondroradionecrosis was made. Characteristics of the primary tumor, chondroradionecrosis grade, number of biopsies needed to rule out recurrence, and laryngectomy indications were ana-lyzed. The possible predisposing factors such as alcohol and tobacco use and othermajor chronic diseases were investigated. Results: All of the patients had a history of smoking. The most common comorbiditywas hypertension (46.2%), followed by chronic obstructive pulmonary disease (23.1%).The onset of symptoms was documented within the 10 months following the radiationtherapy in 12 of the patients (93.3%) and 12 years after the primary radiation therapy in 1 patient. As the most common symptom, fetor oris was observed in all of the patients, followed by dysphagia (69.2%), hoarseness (61.5%), pain (53.8%), dyspnea (46.2%), andnecrotic fistula formation in the anterior neck (15.4%) consecutively. Tumor suspicion(84.6%) was the most common indication for laryngectomy followed by chronic aspi-ration or feeding disorder (61.5%). Twelve patients were treated with total and 1 with supraglottic laryngectomy. Pectoralis major muscle flap was used in all of the patients for pharyngeal reconstruction or protection against salivary fistula. Conclusion: Diagnosis of chondroradionecrosis is challenging, and tumor recurrenceshould always be kept in mind. Patients must be informed about the possibility of chondroradionecrosis complications including laryngectomy. Introduction: Chondroradionecrosis is a rare and the most severe complication of radi- ation therapy for laryngeal carcinoma.